Sample Entropy Signatures: A new way to interpret SampEn values[Formula presented] - Rozendo, Guilherme Botazzo [UNESP]; do Nascimento, Marcelo Zanchetta; Roberto, Guilherme Freire; de Faria, Paulo Rogério; Silva, Adriano Barbosa; Tosta, Thaína Aparecida Azevedo; Neves, Leandro Alves [UNESP] (Elsevier, 2022)
We present the Sample Entropy Signatures method, which provides a new way to represent images via Sample entropy (SampEn). The proposed method defines texture signatures from multiple SampEn values obtained from combinations of the parameters m and r. Here, m signatures were determined (m ranging from 1 to 4), with r points each (r ranging from 0.06 to 0.4), and the behavior of each signature was determined by the metrics: area under the curve, skewness, maximum entropy value, and area ratio. This approach aimed to improve the quantitative capacity of SampEn and provide a new interpretation of its values.
Keywords: Feature extraction; Pattern recognition; SampEn signatures; Sample entropy; Signature metrics; Texture signatures